Cut from the Same Cloth? A Comparative Study of Domestic Extremists and Gang Members in the United States. (2nd January 2018) - Pyrooz, David C.; LaFree, Gary; Decker, Scott H.; James, Patrick A.
Abstract : Despite calls for research on the similarities and differences between violent extremist groups and criminal street gangs, there have been few empirical comparisons. We develop a comparative model that emphasizes explicit, spurious, and indirect linkages between the two groups and use national sources of data on domestic extremists and gang members—the Profiles of Individual Radicalization in the United States (PIRUS) and the National Longitudinal Survey of Youth 1997 (NLSY97)—to compare them across group involvement, demographic, family, religion, and socioeconomic status characteristics. Six percent of domestic extremists in PIRUS have a history of gang ties, which constitutes a minimal proportion of domestic extremists and is likely the rare exception among the population of gang members. Gang extremists more closely resemble non-gang extremists in PIRUS than they do gang members in the NLSY97. While these groups have some similarities, one of the major differences is that gang members are younger than domestic extremists. This likely contributes to many of the other differences between the groups across the life course, including marriage, parenthood, unemployment, and education. Given that the evidence is most consistent with the independence model, further comparative testing is needed before generalizing gang-related policies and programs to domestic extremism.